Review of the genus Prionispa Chapuis, 1875 (Coleoptera Chrysomelidae: Cassidinae: Oncocephalini) of the Philippines - Calcetas, Orlando A. (Philippine Journal of Science, 2023)
The genus Prionispa Chapuis, 1875 (Coleoptera: Chrysomelidae: Cassidinae: Oncocephalini) is reviewed in the Philippines. Four species from the Philippines are treated. Keys to the genera and species of Prionispa is provided.